Difference analysis of shale gas-bearing property —a case study of the shale within lower Cambrian Niutitang Formation on the margin of palaeouplift - Ge, Mingna; Bao, Shujing; Wang, Yufang; Li, Haohan; Wang, Ting; Liang, Hongbo (Frontiers in Earth Science, 2025)
IntroductionShale gas has become an important field for increasing oil and gas reserves and production in China. The breakthrough of Cambrian shale gas in Sichuan Basin provides guidance for the exploration of shale gas in southern China. However, the Niutitang Formation shale on the periphery of Sichuan Basin exhibits multiple depositional subfacies and complex structural styles, and the factors of gas diversity are not clear.MethodsBy the methods of organic geochemistry experiment, reservoir physical property test and gas content test, combined with the hydrocarbon generation history and structural evolution history data, the gas content difference is analyzed of Hannan palaeouplift, Shennongjia palaeouplift, Huangling palaeouplift and Xuefengshan palaeouplift.ResultsThe organic matter type of Niutitang Formation shale is mainly type I, the average organic carbon content is 1.50%–3.56%, the average Ro is 2.37%–3.90%, the brittle minerals are mainly quartz that the content is 28%–53%, and the average porosity is 0.51%–3.34%. The pores contain organic pores, inorganic pores and micro-fractures, and the fractures are mostly filled with calcite. Gas content 0.13m³/t–4.19m³/t. Through comparative analysis of main controlling factors affecting gas content of shale, the causes of gas diversity of Niutitang Formation shale are identified.Discussion(1) the differences in preservation conditions caused by structural strength, fracture development degree and the coupling relationship with tectonic fractures are the key factors restricting the gas content of shale. (2) Early deep burial time, long deep burial time and fast deep burial are the key factors that cause the difference of thermal evolution degree of shale. (3) The difference of hydrocarbon generation potential caused by sedimentary subfacies in the same facies zone is an important factor restricting the gas generation capacity of shale. (4) The areas with the lower Plate of thrust nappe, the degree of thermal evolution is less than 3.0%, and the deepwater facies of trough are favorable directions for further exploration. This study will provides reference significance for shale gas exploration of Cambrian Niutitang Formation in the complex structural area periphery of Sichuan Basin in south China.